Invariant NKT Cell Defects in Vitamin D Receptor Knockout Mice Prevents Experimental Lung Inflammation - Yu, Sanhong (2011)
Vitamin D receptor (VDR) deficiency (knockout, KO) results in a failure of mice to generate an airway hyper-reactivity (AHR) response on both the Balb/c and C57BL/6 background. The cause of the failed AHR response is the defective population of iNKT cells in the VDR KO mice since wildtype (WT) iNKT cells rescued the AHR response. VDR KO mice had significantly fewer iNKT cells and normal numbers of T cells in the spleen compared to WT mice. In Balb/c VDR KO mice the reduced frequencies of iNKT cells was not apparent in the liver or thymus. VDR KO and WT Th2 cells produced similar levels of IFN-γ, and IL-5. On the Balb/c background Th2 cells from VDR KO mice produced less IL-13 while on the C57BL/6 background Th2 cells from VDR KO mice produced less IL-4. Conversely, VDR KO iNKT cells were defective for the production of multiple cytokines (Balb/c IL-4, IL-5, and IL-13; C57BL/6 IL-4, and IL-17). Despite relatively normal Th2 responses Balb/c and C57BL/6 VDR KO mice failed to develop AHR responses. The defect in iNKT cells as a result of the VDR KO was more important than the highly susceptible Th2 background of the Balb/c mice. Defective iNKT cell responses in the absence of the VDR result in the failure to generate AHR responses in the lung. The implication of these mechanistic findings for human asthma requires further investigation.